The Result of Second Field Test of Cellulose Degrading Bacteria from Mangrove Soil Microbiology Handout - Nugraheni, Febriani Sarwendah Asri; Hastuti, Utami Sri; Rohman, Fatchur (Universitas Sembilanbelas November Kolaka, 2020)
Learning media is one of the most important component in a learning process, both inside or outside a classroom. In order to provide proper learning for students based on the researcherâ€™s prior research, at least, three different field tests are needed. This research is a quasi-experiment, which is provide result of the second field test of cellulose degrading bacteria from mangrove soil microbiology handout both in cognitive and psychomotor ability. The research aims are to describe effect of this microbiology handout on studentâ€™s cognitive achievement and gain data about inappropriate laboratory written instruction in this handout. Data gained by conducting learning activities using developed handout which were 2 times in class theory and three times of practical activity using instuctions written in the handout. In the end of class theory activity, students did a posttest to confirm their improvement of cognitive ability while their practical ability was observed using observation sheet along with their activities. Results showed that handout which being tested could improve student cognitive at average level (n gain 0,419). In contrast, several parts of laboratory written instruction need to be fixed to make better microbiology handout.Â